Genomic Insights into the Population History of the Resande or Swedish Travelers. (19th January 2023) - Vilà-Valls, Laura; Aizpurua-Iraola, Julen; Casinge, Sebastian; Bojs, Karin; Flores-Bello, André; Font-Porterias, Neus; Comas, David
Abstract: The Resande are a minority ethnic group in Sweden, who were characterized by an itinerant way of life, and they have been suggested to originate from the mixture between Swedish and Romani populations. Because the population history of the Resande has been scarcely studied, we analyzed genome-wide genotype array data from unrelated Resande individuals in order to shed light on their origins and demographic history for the first time from a genetic perspective. Our results confirm the Romani-related ancestry of this population and suggest an admixture event between a Romani-like population and a general Swedish-like population that occurred approximately between the mid-18th and mid-19th centuries, two centuries after the arrival of the first historically reported Romani families in Sweden. This inferred date suggests that the Romani group involved in the admixture is related to the pre-18th-century arrivals of Romani in Scandinavia. In addition, a reduction in the population size is detected previous to the admixture event, suggesting a subtle signal of isolation. The present work constitutes a step forward toward a better representation of ethnic minorities and underrepresented groups in population genetic analyses. In order to know in more detail the complete history of human populations, it is time to focus on studying populations that have not been previously considered for a general scenario and that can provide valuable information to fill in the gaps that still remain uncovered.